Microstructural evolution of Ti–Mo binary alloy via thermohydrogen treatment - Caizong Pan; Aiqi Lu; Qian Wang; Shangzhou Zhang; Zhenhua Meng (Journal of Materials Research and Technology)
The microstructural evolution of Ti–Mo alloys via thermohydrogen treatment and the orientation relationships (ORs) between δ-hydride precipitates and the α-phase were investigated. Results indicated that increasing Mo and hydrogen content elevate the β-phase volume fraction while reducing twin density within the α-phase. This promotes a transition from twisted fibrous to straight basket-weave microstructures, and induces overall microstructural refinement following thermohydrogen treatment. Two distinct δ-hydrides types precipitate in association with the β-phase, and their volume fractions decrease with Mo addition due to enhanced solid solubility of hydrogen in the matrix and suppressed hydrogen diffusion. Four orientation relationships between δ-hydrides and α-phase are characterized. The {101‾0} and {101‾3} planes are favorable for OR1 and OR2 δ-hydrides with elongated morphology, accompanying extensive twin formation. The OR3 and OR4 δ-hydrides typically appear fine short lamellae on the {101‾1} and {1‾011} planes. The reason is analyzed in terms of microstructure characterization, lattice strain analysis, and interface mismatch calculations.